HISPANOAMERIŠKI POSTMODERNIZEM (Philological Studies, 2019)
The hispano-american prose of today is a part of the global cultural and ideological context of postmodernism involving several directions which the postmodern literary theory can hardly evaluate or classify. In hispano-american literature the joyful labels like the literary "boom" of the sixties or seventies or the »post boom« of the eighties can no longer be found. Terms like “post-magic realism”, “postBorges' way of writing” or “post colonialism” are preferred though not yet clearly defined. History of literature today cannot determine the period and directions as clearly as in the past when the criteria of analysis and evaluation were fluctuating between tradition and innovation.